2018
DOI: 10.1111/mec.14697
|View full text |Cite
|
Sign up to set email alerts
|

Among‐year variation in selection during early life stages and the genetic basis of fitness in Arabidopsis thaliana

Abstract: Incomplete information regarding both selection regimes and the genetic basis of fitness limits our understanding of adaptive evolution. Among-year variation in the genetic basis of fitness is rarely quantified, and estimates of selection are typically based on single components of fitness, thus potentially missing conflicting selection acting during other life-history stages. Here, we examined among-year variation in selection on a key life-history trait and the genetic basis of fitness covering the whole lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 66 publications
(163 reference statements)
2
31
1
Order By: Relevance
“…In their native habitats, the two populations are exposed to widely different climates and also to differences in seasonal changes of day length. Previous work has demonstrated that the relative survival of the Italian genotype in Sweden is negatively related to minimum soil temperature in winter 15 , and also that genetic differences in phenological traits such as timing of germination and flowering can explain a substantial portion of selection against the non-local genotype at the two sites 51, 52, 53 . Taken together, our data indicate that differences in climate have been more important than differences in soil and endogenous microbiota for the adaptive divergence between the two study populations.…”
Section: Discussionmentioning
confidence: 99%
“…In their native habitats, the two populations are exposed to widely different climates and also to differences in seasonal changes of day length. Previous work has demonstrated that the relative survival of the Italian genotype in Sweden is negatively related to minimum soil temperature in winter 15 , and also that genetic differences in phenological traits such as timing of germination and flowering can explain a substantial portion of selection against the non-local genotype at the two sites 51, 52, 53 . Taken together, our data indicate that differences in climate have been more important than differences in soil and endogenous microbiota for the adaptive divergence between the two study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although we obtained data for the full life cycle of the two parental species and their F1 hybrids, our field experiment only looked 447 at a single habitat type in a single year. This has given us valuable insight into the fitness of these 448 first-generation hybrids, suggesting that they can perform as well as the parent with the best 449 performance in this given situation, but more field transplants are needed to cover the full range of 450 habitat types and to account for variability among years (Postma & Ågren, 2018). Since the 451 formation and establishment of F1 hybrids are clearly not a bottleneck, we will focus our future 452 work on advanced hybrids, including F2 and backcrosses, but also hybrids in natural populations, 453 not only to determine fitness in transplant experiments, but also to identify introgressed loci 454 involved in local adaptation (Martin et al, 2006;Suarez-Gonzalez et al, 2018).…”
Section: Effects Of Fertilizer Addition 429mentioning
confidence: 99%
“…This gives the advantage of being able to replicate the same genotype in several environments, but the downside is that part of the life cycle, from seed to established young plant, is missing. This can be justified for long‐lived species, but for annual species, including the seed stage is crucial in understanding local adaptation (Postma & Ågren, ).…”
Section: Introductionmentioning
confidence: 99%
“…This can be justified for long-lived species, but for annual species, including the seed stage is crucial in understanding local adaptation (Postma & Ågren, 2018).…”
mentioning
confidence: 99%